2020
DOI: 10.21203/rs.3.rs-22876/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic Profiling of Ocular Surface Microbiome Changes in Meibomian Gland Dysfunction

Abstract: Background: Ocular surface microbiome changes can affect meibomian gland dysfunction (MGD) development, which in turn may increase the risk of tissue infection. To delineate what these changes are, we used shot-gun metagenomic analysis to determine if there are differences between the microbial communities in ocular sites surrounding the meibomian gland in healthy and patients afflicted with MGD. This comparison entailed comparing the microbe content in different microbiomes of the eyelid skin, conjunctiva and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…In previous studies, the richness of the conjunctival sac microbiome in patients with dry eyes was inconsistent. While some studies revealed an increased number of bacteria (18,19), most studies were in accordance with our study that patients with dry eyes have diminished ocular surface microbiome diversity (20)(21)(22)(23). In studies regarding SS, bacterial diversity was diminished both for the oral mucosa (24) and the ocular surface (23).…”
Section: Discussionsupporting
confidence: 90%
“…In previous studies, the richness of the conjunctival sac microbiome in patients with dry eyes was inconsistent. While some studies revealed an increased number of bacteria (18,19), most studies were in accordance with our study that patients with dry eyes have diminished ocular surface microbiome diversity (20)(21)(22)(23). In studies regarding SS, bacterial diversity was diminished both for the oral mucosa (24) and the ocular surface (23).…”
Section: Discussionsupporting
confidence: 90%
“…YG1 is a lignin model dimer-metabolizing bacterium newly isolated from sediment and has never been reported on the ocular surface (Ohta, 2018). However, the genus Sphingobium had been reported to be abundant in the MGD meibum (Zhao et al, 2020). Interestingly, the correlation between species abundances and clinical parameters in the DB group showed higher RAs of Delftia tsuruhatensis, Sphingobium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that alteration in the ocular surface microbiota is involved in DED (Gomes et al, 2020). However, the majority of prior studies have focused on specific types of DED, such as MGD and Sjögren's syndrome (de Paiva et al, 2016;Watters et al, 2017;Jiang et al, 2018;Dong et al, 2019;Zhao et al, 2020). In contrast, patients with other types of DED were less represented, especially those with a mixed type of diagnosis.…”
Section: Introductionmentioning
confidence: 99%